Academic support model for post-secondary school students with learning disabilities: student and instructor perceptions. Issue 2 (1st February 2019) - Lipka, Orly; Forkosh Baruch, Alona; Meer, Yael
ABSTRACT: While post-secondary school students with learning difficulties confront many challenges, there is little research on methods of support. In the current study, the 'adapted course' model was qualitatively examined from the perspective of both students and instructors. The main goal was to explore how students and instructors perceived the instruction in adapted courses. Five pre-service students with learning disabilities (LD) and/or attention-deficit hyperactivity disorder and three instructors were interviewed. Responses were analysed using subjective analysis, with central content categories identified based on student and instructor statements. Six main themes emerged: (1) small class size; (2) emotional support; (3) adjusted teaching methods; (4) independent practice exercises; (5) instruction by modelling; and (6) instructor characteristics. The current study can inform pedagogical principles on which a support model for post-secondary students with LD can be based. It provides analyses of the effectiveness of one support model and presents the perceptions of both faculty and students. Moreover, the study provides an opportunity to learn about potential components of effective teaching-learning, not only in the specific context of adapted courses, but in any supportive learning situation (e.g. tutoring) or course.